SIFAT KIMIA DAN ORGANOLEPTIK BAKSO DAGING KERBAU DENGAN PENAMBAHAN TEPUNG TALAS LOKAL PADA LEVEL BERBEDA - Ria Anjalani; Maria Haryulin Astuti; Febriana Dewi Pertiwi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2020)
This study aimed to find out the effect of adding local taro flour at different levels on the chemical and organoleptik properties of buffalo meatballs. This study used a Completely Randomized Design with 5 treatments and 4 replications for each treatment i.e. P0 (100% tapioca flour), P1 (87,5% tapioca flour and 12,5% taro flour), P2 (75% tapioca flour and 25% taro flour), P3 (62,5% tapioca flour and 37,5% taro flour), and P4 (50% tapioca flour and 50% taro flour). Chemical properties of buffalo meatballs were analyzed with variance analysis and further results were evaluated by Tukey Test. Organoleptic properties of buffalo meatballs were analyzed non parametrically by Friedman Test. The difference percentage of taro flour showed a significant different on dry matter and protein content of buffalo meatballs (P<0.05). However, it showed a non significant difference on fat content of buffalo meatballs (P>0.05). The difference percentage of taro flour also showed a non significant difference on organoleptic properties of buffalo meatballs (P>0.05). The best of dry matter, protein, and fat content were obtained in P0 and P2 at 30.51%; 9.08%; and 1.13%, respectively. Color, taste, and flavor of meatballs were preferred by panelists in P0. Texture and elasticity of meatballs were preferred by panelists in P1.